Genetic moderation of cocaine subjective effects by variation in the TPH1, TPH2, and SLC6A4 serotonin genes. (October 2017) - Patriquin, Michelle A.; Hamon, Sara C.; Harding, Mark J.; Nielsen, Ellen M.; Newton, Thomas F.; De La Garza, Richard; Nielsen, David A.
Abstract : Objective: This study investigated variants of tryptophan hydroxylase ( TPH ) 1, TPH2, and SLC6A4 in the moderation of the subjective effects of cocaine. Methods: Non-treatment-seeking cocaine-dependent individuals ( N =66) were intravenously administered saline and cocaine (40 mg) in a randomized order. Participants self-reported subjective effects of cocaine using a visual analog scale starting before administration of saline or cocaine (−15 min) to up to 20 min after infusion. Self-report ratings on the visual analog scale ranged from 0 (no effect) to 100 (greatest effect). Participants were genotyped for the TPH1 rs1799913, TPH2 rs4290270, and SLC6A4 5-HTTLPR variants. Repeated-measures analysis of covariance was used to examine changes in subjective effect scores over time while controlling for population structure. Results: Participants carrying the TPH1 rs1799913 A allele reported greater subjective response to cocaine for 'stimulated' and 'access' relative to the CC genotype group. Those carrying the TPH2 rs4290270 A allele reported higher 'good effect' and lower 'depressed' effect relative to the TT genotype group. Those carrying the SLC6A4 5-HTTLPR S′ allele reported greater 'desire' and 'access' compared with the L′L′ genotype group. Conclusion: These findings indicate that TPH1, TPH2, and SLC6A4 variants moderate the subjective effects of cocaine in non-treatment-seeking cocaine-dependent participants.